The influence of flexible work arrangement and remuneration on employees’ job satisfaction in private higher education institutions / Abdul Kadir Othman …[et al.] - Othman, Abdul Kadir; Mustafa, Hasfah Nurhanum; Hamzah, Muhammad Iskandar; Abdullah, Mohd Zulkifli (Universiti Teknologi MARA, Shah Alam, 2019)
Job satisfaction is the most common topic of research, but it is still relevant as most problems in the workplace are related to employees’ job satisfaction. The same problem is also prevalent those working in higher educational institutions. Due to this concern, the present study was conducted among 163 academics in private colleges in Kuantan, Pahang, Malaysia. Based on the result of factor analysis, it was found that job satisfaction of academics can be divided into four dimensions; career and salary satisfaction, creativity satisfaction, administration satisfaction and attitudinal satisfaction. Factors that significantly influence the dimensions of job satisfaction are flexible work arrangement, salary and promotion. All these three factors significantly influence career and salary satisfaction and administration satisfaction. Promotion on the other hand leads to creativity satisfaction. And, salary contributes to attitudinal satisfaction. The findings of the study indicate the importance of flexible work arrangement and compensation on academics’ satisfaction, thus, the management should consider these aspects when planning for the work schedule and career development of the academics in the institutions of higher learning.